2013
DOI: 10.1371/journal.pone.0072961
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Biogeochemistry in the Caribbean Sponge, Xestospongia muta: A Source or Sink of Dissolved Inorganic Nitrogen?

Abstract: BackgroundSponges have long been known to be ecologically important members of the benthic fauna on coral reefs. Recently, it has been shown that sponges are also important contributors to the nitrogen biogeochemistry of coral reefs. The studies that have been done show that most sponges are net sources of dissolved inorganic nitrogen (DIN; NH4 + and NO3 −) and that nitrification, mediated by their symbiotic prokaryotes, is the primary process involved in supplying DIN to adjacent reefs.Methodology/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
132
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 66 publications
20
132
0
Order By: Relevance
“…; calculated from data in Fiore et al 2013, their Table 1) is double the mean pumping rate found in the present study. This is the first study since the work of Reiswig (1974) to directly investigate the relationship between spongocoel morphology and excurrent flow.…”
Section: Excurrent Seawater Velocities and Sponge Morphologysupporting
confidence: 58%
See 3 more Smart Citations
“…; calculated from data in Fiore et al 2013, their Table 1) is double the mean pumping rate found in the present study. This is the first study since the work of Reiswig (1974) to directly investigate the relationship between spongocoel morphology and excurrent flow.…”
Section: Excurrent Seawater Velocities and Sponge Morphologysupporting
confidence: 58%
“…For example, Baikalospongia bacillifera and B. intermedia from Lake Baikal, Russia, were found to re move 1870 mg C d −1 m −2 of prokaryotic picoplankton, resulting in a picoplankton-depleted layer of water within 1 m of the benthos, but were a source of 750 mg C d −1 m −2 of eukaryotic picoplankton (Pile et al 1997). Sponges are also important in nitrogen cycling and release large amounts of dissolved inorganic nitrogen that may influence levels of primary production on coral reefs (Southwell et al 2008, Fiore et al 2013. Mass mortality of the Florida Bay sponge community resulted in an increase in the average water column turnover rate by as much as 12 d for some regions of the Bay and could account for the increased algal blooms reported there (Peterson et al 2006).…”
Section: Photo: Steven Mcmurraymentioning
confidence: 99%
See 2 more Smart Citations
“…Their ecosystem engineering roles are enabled by diverse communities of symbiotic prokaryotes that can account for up to 40% of the sponge body volume (Taylor et al, 2007a,b;Webster et al, 2010;Hentschel et al, 2012). The symbionts extend the metabolic capabilities of the host by mediating processes, such as photosynthesis (Wilkinson, 1983;Arillo et al, 1993;Steindler et al, 2002), carbon (De Goeij et al, 2008a,b;de Goeij et al, 2013), nitrogen (Wilkinson and Fay, 2004;Mohamed et al, 2008;Southwell et al, 2008a;Hoffmann et al, 2009;Schläppy et al, 2010;Fiore et al, 2013), methane (Vacelet et al, 1995), sulfur (Hoffmann et al, 2005), and phosphorus (Sabarathnam et al, 2010;Zhang et al, 2015b) cycling. Metagenomic and transcriptomic studies of sponge microbiomes have provided independent molecular evidence of the contribution of symbiotic bacteria, in particular, to biogeochemical and nutrient cycling Fiore et al, 2015;Rua et al, 2015), underscoring the significance of the holobiont perspective in understanding ecological roles of animal hosts in marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%